Pembuatan Aplikasi “Warung Keluarga” Sebagai Aplikasi E-Commerce Berbasis Web dan Mobile - Deryan Gelrandy; Oky Dwi Nurhayati; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
In the rapid development of industry, the process of buying and selling has been convenient to do. Recently, consumers who need to buy some goods could easily look for it in online store. Furthermore, seller who perceive that either want to sell their stuff which could not be used anymore or seek additional income may sell their stuff through this online store. The benefit that makes this process much easier is the transaction could exist even though seller and buyer do not interact face-to-face. However as this process is too easy, it poses a shortage that may causes a trickery. In the implementation, buyer will purchase goods in online store web site without aware of the seller. Therefore, it is important to make an e-commerce app where every seller has clear identity. The makings of this app aim to enhance security in sales and purchase transaction since SMA N 3 Semarang alumni only who could be a seller so that buyer will feel secure in doing transaction. This app also could be a platform to collect some information about the alumni because there is detail information that can facilitate in holding an alumni reunion. This app uses C# language programming, ASP.NET, Visual Studio and SQL Server database. The result of this app will be implemented for SMA N 3 Semarang.